PEMBERDAYAAN EKONOMI MASYARAKAT PETANI JAGUNG BERBASIS KELOMPOK USAHA TANI DI KABUPATEN TAKALAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The main problem in this study is how to empower the corn farming community based on farming groups in Takalar Regency with the aim of (1) To find out the process of economic empowerment of the corn farming community based on farming groups in Takalar Regency, (2) To find out the obstacles to economic empowerment of farming communities. The corn-based farming group in Takalar Regency. The results of this study indicate that the process of economic empowerment of the corn farming community based on farming groups in Barugaya Village is through deliberation that has been successfully carried out by the government supported by the community who are members of farmer groups then counseling and training is carried out by the agricultural office and finally carried out capacity development in empowerment through farmer groups, but several obstacles that occur are low public awareness to participate, limited budget funds, uncertain market prices, and uncertain weather.